The conundrum of current anti-SARS-CoV-2 vaccines - Federico, Maurizio (Cytokine Growth Factor Rev, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has given rise to the urgent need for vaccines and therapeutic interventions to address the spread of the SARS-CoV-2 virus. SARS-CoV-2 vaccines in development, and those being distributed currently, have been designed to induce neutralizing antibodies using the spike protein of the virus as an immunogen. However, the immunological correlates of protection against the virus remain unknown. This raises questions about the efficacy of current vaccination strategies. In addition, safety profiles of several vaccines seem inadequate or have not yet been evaluated under controlled experimentation. Here, evidence from the literature regarding the efforts already made to identify the immunological correlates of protection against SARS-CoV-2 infection are summarized. Furthermore, key biological features of most of the advanced vaccines and considerations regarding their safety and expected efficacy are highlighted.